THE MAKING OF PROFILE VIDEO ABOUT TOURISM IN SIAK REGENCY - Sikin Nuratika; Safra Apriani Zahraa; M I Gunawan (Politeknik Negeri Bengkalis, 2019)
Tourism is very important in Indonesia. However, there are many ways to promote tourism. One of the ways is through video. In promoting tourism in Siak Regency, many people have made tourism video but only in short videos. They are advertisement videos. The duration of the videos was limited and the dubber explained the exposure of the video used Bahasa Indonesia. Therefore, this profile video about tourism in Siak Regency will help Siak Regency in promoting tourism destinations. The main purpose of this final project is to explain the processes of making a profile video about tourism in Siak Regency. The method of this study is descriptive method. There are several steps in making this video such as collecting data, providing materials recording the video, giving the subtitles, continuing proceed with the process of dubbing, and the last was editing process. This video contains of ten places and a tourism event. This video can be used in order to help students, Tourism Office of Siak Regency, local community, and especially International community get information about the history and the tourism destinations in Siak Regency easily.Â Â Â Tourism is very important in Indonesia. However, there are many ways to promote tourism. One of the ways is through video. In promoting tourism in Siak Regency, many people have made tourism video but only in short videos. They are advertisement videos. The duration of the videos was limited and the dubber explained the exposure of the video used Bahasa Indonesia. Therefore, this profile video about tourism in Siak Regency will help Siak Regency in promoting tourism destinations. The main purpose of this final project is to explain the processes of making a profile video about tourism in Siak Regency. The method of this study is descriptive method. There are several steps in making this video such as collecting data, providing materials,iirecording the video, giving the subtitles, continuing proceed with the process of dubbing, and the last was editing process. This video contains of ten places and a tourism event. This video can be used in order to help students, Tourism Office of Siak Regency, local community, and especially International community get information about the history and the tourism destinations in Siak Regency easily.